Predicting Coparenting Quality in Daily Life in Mothers and Fathers - McDaniel, Brandon T. (J Fam Psychol, 2018)
The purpose of the current study was to examine contextual (daily relationship quality, daily stressors, daily work hours), parent (daily negative emotions, gender), and child factors (daily child-induced parenting stress) as predictors of mothers’ and fathers’ perceptions of daily coparenting quality. Mothers and fathers from 174 families completed a 14-day diary study. Utilizing multilevel modeling, our results suggest that daily coparenting is multiply determined. Indeed, daily fluctuations in coparenting were predicted by similar daily fluctuations in couple relationship quality, parent negative mood, parenting stress, and father work hours. Moreover, as daily risk factors accumulated the quality of daily coparenting deteriorated further, suggesting that a buildup of stressors and daily difficulties may be particularly detrimental to parents’ abilities to cooperate with one another and coordinate their parenting together on a daily basis. Overall, our results suggest that there are many avenues through which we can intervene in the family system to improve the quality of daily coparenting.